Pulmonary Hypertension due to a Pulmonary Artery Leiomyosarcoma: A Case Report - Seyyed Hassan Adeli; Bardia Nemati; Mahboubeh Jandaghi; Mohammad Mahdi Riahi; Fatemeh Hosseinzadeh; Fatemeh Salarvand (Case Reports in Pulmonology)
Background. Primary pulmonary artery sarcomas are very rare and their histologic type, called leiomyosarcoma, is even rarer. Case Report. A 64-year-old woman presented with progressive weakness, fatigue, malaise, and dyspnea, and a marked elevation of pulmonary artery pressure was admitted. She was initially diagnosed with chronic pulmonary thromboembolism and chest computed tomography (CT) scan revealed that lobulated heterogeneous left hilar mass extended to precarinal and subcarinal space. MRI demonstrated a polypoid lesion at trunk with extension to left main pulmonary artery and its first branch. She was operated, a yellowish-shiny solid mass in pulmonary trunk was seen intraoperatively, and pulmonary endarterectomy was performed. Her tumor was pathologically diagnosed as pulmonary artery leiomyosarcoma. She died 3 months later after one chemotherapy course. Conclusion. Initially, the patient underwent surgery due to pulmonary embolism but, during the operation, the observed mass increased the probability of pulmonary artery neoplasm. Clinicians must consider pulmonary artery sarcoma when making the differential diagnosis for patients with pulmonary arteries masses. In addition to clinical prediction scores and CT and MRI findings to identify the patients with pulmonary artery sarcoma, PET scanning is the diagnosis of choice in differentiating embolism and neoplasm and is strongly recommended in these patients.